2011
DOI: 10.1158/0008-5472.can-10-3978
|View full text |Cite
|
Sign up to set email alerts
|

Antihelminth Compound Niclosamide Downregulates Wnt Signaling and Elicits Antitumor Responses in Tumors with Activating APC Mutations

Abstract: Wnt/β-catenin pathway activation caused by APC mutations occurs in approximately 80% of sporadic colorectal cancers. The anti-helminth compound niclosamide downregulates components of the Wnt pathway, specifically Dishevelled-2 (Dvl2) expression, resulting in diminished downstream β-catenin signaling. In this study, we determined if niclosamide could inhibit the Wnt/ β-catenin pathway in human colorectal cancers and whether its inhibition might elicit antitumor effects in the presence of APC mutations. We foun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
258
3
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(280 citation statements)
references
References 31 publications
10
258
3
9
Order By: Relevance
“…The anthelmintic activity of niclosamide seems to rely on its ability to uncouple mitochondrial oxidative phosphorylation (61). More recently, it has been found to inhibit proliferation of some tumor cells by hampering different regulatory pathways, without relevant effects on normal nontumor cells (62)(63)(64). Notably, niclosamide has also been reported to act as an antimycobacterial agent (64), plausibly disrupting Mycobacterium membrane potential and pH homeostasis (65).…”
Section: Discussionmentioning
confidence: 99%
“…The anthelmintic activity of niclosamide seems to rely on its ability to uncouple mitochondrial oxidative phosphorylation (61). More recently, it has been found to inhibit proliferation of some tumor cells by hampering different regulatory pathways, without relevant effects on normal nontumor cells (62)(63)(64). Notably, niclosamide has also been reported to act as an antimycobacterial agent (64), plausibly disrupting Mycobacterium membrane potential and pH homeostasis (65).…”
Section: Discussionmentioning
confidence: 99%
“…1E). Niclosamide is an established antihelminthic drug for which recent work in extra-neural, for example, preclinical colorectal cancer models had already suggested antineoplastic activity (21,22). This encouraged further assessment as a candidate compound for glioblastoma therapy.…”
Section: Niclosamide Is a Previously Unrecognized Candidate For Gliobmentioning
confidence: 99%
“…Evidence from previous studies had suggested that niclosamide interfered with several of these in non-neural cancer cells, specifically affecting the NOTCH-, mTOR-, WNT-/CTNNB1-, and NF-kB signaling cascades (21,22,(31)(32)(33). We focused on these cascades for mechanism of action analysis.…”
Section: Niclosamide Interferes With Cancer-driving Signaling Cascadesmentioning
confidence: 99%
“…Amongst other functions, Niclosamide was found to inhibit Wnt/Frizzled-1 signaling with an IC 50 of 0.5 ± 0.05 μM [253][254][255]. It also downregulates Dishevelled-2 (Dvl-2) [256] and induces LRP6 degradation in prostate and breast cancer cells [254]. Interestingly, Niclosamide has no reported toxicity against non-cancer cells [256].…”
Section: The Wnt Receptor Complexmentioning
confidence: 99%
“…It also downregulates Dishevelled-2 (Dvl-2) [256] and induces LRP6 degradation in prostate and breast cancer cells [254]. Interestingly, Niclosamide has no reported toxicity against non-cancer cells [256].…”
Section: The Wnt Receptor Complexmentioning
confidence: 99%